Ceramic‐based dielectric metamaterials. Issue 1 (17th January 2022) - Luo, Weijia; Yan, Sen; Zhou, Ji
Abstract: Dielectric metamaterials based on ceramics have attracted considerable interest in the past few years owing to their low dielectric loss, simple structure, excellent multifield tunability, and good environmental adaptability. They are considered to be promising alternative to metal‐based metamaterials and can lead to a new strategy for the development of passive devices. In this review, the recent progress of ceramic‐based dielectric metamaterials in electromagnetic applications, energy applications, non‐Hermitian systems, and natural materials with near‐zero or negative refraction are summarized. The design principle and mechanism, as well as manufacturing technologies, are also introduced, and the current development trend of ceramic‐based dielectric metamaterials are proposed. Abstract : In this review, the recent progress of ceramic‐based dielectric metamaterials are summarized. The design principle and mechanism, as well as manufacturing technologies, are also introduced, and the current development trend of ceramic‐based dielectric metamaterials are proposed.